Promosi Kesehatan Untuk Meningkatkan Pengetahuan dan Keterampilan Ibu Menyusui Dalam Perilaku Pemberian ASI Eksklusif di RS Hl Manambai Abdulkadir - Evi Gustia Kesuma; Luh Putu Sri Yuliastuti (FKIP, Universitas Palangka Raya, 2023)
Exclusive breastfeeding reduces infant mortality rates caused by various diseases that commonly afflict children such as diarrhea and pneumonia. Babies with exclusive breastfeeding will have a stronger immune system compared to babies who are given formula milk. Breast milk provides protection to babies against various diseases, especially infectious diseases. According to RISKESDAS 2021, 52.5 percent or only half of the 2.3 million infants aged less than six months are exclusively breastfed in Indonesia, or a decrease of 12 percent from the figure in 2019. The highest coverage of exclusive breastfeeding is in West Nusa Tenggara with coverage of 81.46% and coverage of exclusive breastfeeding in Sumbawa Regency of 89.3. This of course encourages us to strive to maintain and even increase the scope of exclusive breastfeeding to increase children's intelligence. Objective: Increase the knowledge and skills of breastfeeding mothers towards exclusive breastfeeding for babies. Method: The method used in increasing this knowledge is by Audiovisual media, namely presenting the Understanding, composition, benefits, influencing factors, how to maximize & improve, how to prepare and store breast milk and provide counseling in the form of interactive lectures. Target: The target of this community service activity is from mothers of reproductive age who have babies aged 0 to 6 months at H.L. Manambai Abdulkadir Hospital. Results: The delivery of material with lecture and demonstration methods supports the ability of participants to master the material regarding increasing knowledge and skills in breastfeeding delivered by the community service team so that there is an increase seen from the pretest and posttest given to mothers after the activity takes place.